2020
DOI: 10.1111/odi.13735
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of deep learning for screening dental caries from oral photographs

Abstract: Objectives To develop and evaluate the performance of a deep learning system based on convolutional neural network (ConvNet) to detect dental caries from oral photographs. Methods 3,932 oral photographs obtained from 625 volunteers with consumer cameras were included for the development and evaluation of the model. A deep ConvNet was developed by adapting from Single Shot MultiBox Detector. The hard negative mining algorithm was applied to automatically train the model. The model was evaluated for: (i) classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 40 publications
(48 reference statements)
1
74
1
Order By: Relevance
“…Another promising result of DNN-based caries diagnosis was reported by Zhang et al 14 in 2020. A relatively large dataset of 3,932 photos from patients 14 to 60 years old was examined with ConvNet.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Another promising result of DNN-based caries diagnosis was reported by Zhang et al 14 in 2020. A relatively large dataset of 3,932 photos from patients 14 to 60 years old was examined with ConvNet.…”
Section: Discussionmentioning
confidence: 86%
“…Zhang et al 14 in 2020 developed a ConvNet model for dental caries images taken from phone and manual cameras. In total, 2,507 images were used for the training dataset, and 1,125 others were used for the testing dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang X et al developed ConvNet, which is based on CNN, to identify dental caries from oral images captured with consumer cameras. The result showed that the image-wise sensitivity is good ( Zhang et al, 2020 ). At present, more studies have been conducted on the possibility and accuracy of AI-assisted detection of dental caries, but there are few studies on AI-assisted prediction of the occurrence of dental caries.…”
Section: Applications Of ML In the Dental Oral And Craniofacial Imaging Fieldmentioning
confidence: 99%
“…By contrast, there have been few attempts to apply AI technology to assess clinical images, which can be interpreted as a machine-readable equivalent for visual inspection. This study is the first report of automatic detection and categorization of dental caries [ 10 , 11 , 12 , 13 ] or dental plaque [ 14 ] from clinical photographs. When considering the broad spectrum of pathological findings on dental hard tissue, e.g., caries, erosion or developmental disorders, as well as dental interventions, e.g., sealants, dental restorations or prosthodontic measures, it is evident that CNNs need to be trained separately for each of the aforementioned categories.…”
Section: Introductionmentioning
confidence: 99%